Analisis Dengan Menggunakan Metode Altman Z- Score, Springate (S-Score) Dan Zmijewski Sebagai Signaling Kebangkrutan Pada Perusahaan Manufaktur Sektor Otomotif Yang Terdaftar Di Bei Periode 2015-2017 - Agnes Mega Widiastuti (Universitas Tarumanagara, 2019)
he purpose of this study was to determine the predictions of bankruptcy in the Automotive Sector Manufacturing Companies listed in Indonesia Stock Exchange for the period 2015-2017 based on the results of the Altman Z-score, Springate (S-score) and Zmijewski method analysis. This study uses secondary data, it was the annual financial report of the Automotive Sector Manufacturing Company for the period 2015-2017 using the technique of documentation and analyzed by the Altman Z-score method, Springate (S-score), and Zmijewski. The final results of this study indicate that there is a difference in the percentage of bankruptcy rates of each company from each method used. The results of the prediction of the Altman Z-score bankruptcy method, it was the bankrupt category of 25.00%, the non-bankrupt category of 8.33% and the grey area category of 66.67%. The prediction results of Springate (S-score) bankruptcy method, it was the bankrupt category of 66.67%, and the non-bankrupt category of 33.33%. The prediction results of Zmijewski bankruptcy method, it was the bankrupt category of 8.33%, and the non-bankrupt category by 91.67%.